PERFORMANCE OF RETAIL MSMEs IN THE MIDST OF COMPETITION: THE ROLE OF PRODUCT, SERVICE AND PRICE DIVERSITY IN THE CITY OF PONTIANAK - Tedy, Stiffany; Graceallah, Georgerius (FE Program Studi Manajemen, 2026)
This study aims to analyze how product diversity, service quality, and competitive pricing affect the business performance of retail Micro, Small, and Medium Enterprises (MSMEs) in Pontianak, Indonesia. Retail MSMEs have become a key driver of local economic growth, showing rapid and significant development in recent years, driven by increasing consumer demand.However, growing market competition and shifting consumer behavior have posed significant challenges. Using a quantitative approach, the study investigates how these three marketing variables affect MSME performance. The results reveal that while service quality and competitive pricing positively influence business outcomes, excessive product diversity can have a negative impact. These findings highlight the importance of strategic focus and customer-oriented approaches to remain competitive and sustain growth in a dynamic market